1990
DOI: 10.1901/jeab.1990.53-409
|View full text |Cite
|
Sign up to set email alerts
|

Choice Behavior in Transition: Development of Preference for the Higher Probability of Reinforcement

Abstract: Ten acquisition curves were obtained from each of 4 pigeons in a two-choice discrete-trial procedure. In each of these 10 conditions, the two response keys initially had equal probabilities of reinforcement, and subjects' choice responses were about equally divided between the two keys. Then the reinforcement probabilities were changed so that one key had a higher probability of reinforcement (the left key in half of the conditions and the right key in the other half), and in nearly every case the subjects dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

12
60
2
4

Year Published

1991
1991
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 20 publications
12
60
2
4
Order By: Relevance
“…The original version of melioration theory (Herrnstein & Vaughan, 1980) predicts identical acquisition rates for all conditions with the same difference 00-tween reinforcement probabilities (4)1 -4>2)' Thus, none of these theories predicts the pattern of results obtained by Bailey and Mazur. However, a more recent version of melioration theory (Vaughan, 1985) is much more general in its form, and this version makes no specific predictions about this matter. Bailey and Mazur (1990) showed that their results were consistent with an analysis based on Weber's law. Weber's law states that for any stimulus dimension (probability of reinforcement in this case), two stimuli will 00 more discriminable ifthey differ by a larger percentage.…”
supporting
confidence: 81%
See 4 more Smart Citations
“…The original version of melioration theory (Herrnstein & Vaughan, 1980) predicts identical acquisition rates for all conditions with the same difference 00-tween reinforcement probabilities (4)1 -4>2)' Thus, none of these theories predicts the pattern of results obtained by Bailey and Mazur. However, a more recent version of melioration theory (Vaughan, 1985) is much more general in its form, and this version makes no specific predictions about this matter. Bailey and Mazur (1990) showed that their results were consistent with an analysis based on Weber's law. Weber's law states that for any stimulus dimension (probability of reinforcement in this case), two stimuli will 00 more discriminable ifthey differ by a larger percentage.…”
supporting
confidence: 81%
“…Bailey and Mazur (1990) obtained one acquisition curve from each pigeon subject in each condition of their experiment. Every condition began with a few one-probability sessions, which were followed by one transition session and then several two-probability sessions, In the oneprobability sessions, a single reinforcement schedule assigned reinforcers to either of two response keys, with…”
mentioning
confidence: 99%
See 3 more Smart Citations